2007
DOI: 10.4161/cbt.6.2.3624
|View full text |Cite
|
Sign up to set email alerts
|

Zyflamend®-mediated inhibition of human prostate cancer PC3 cell proliferation: Effects on 12-LOX and Rb protein phosphorylation

Abstract: The multiherb anti-inflammatory product Zyflamend was investigated for its antiproliferative effects on PC3 human prostate cancer cells and eicosanoid metabolism in this prostate cancer cell line. Zyflamend produced a concentration-dependent inhibition of cloned COX-1, COX-2, and 5-LOX enzyme activities, with inhibition of 5-HETE production being greater than that of PGE 2 formation. Applied to intact PC3 cells, Zyflamend was found to be most potent against 12-LOX, followed by 5-LOX and then COX activities. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 39 publications
3
20
0
Order By: Relevance
“…Our data pertaining to Zyflamend and several studies from other laboratories (Bemis et al, 2005;Burke et al, 2015;Capodice et al, 2009;Ekmekcioglu et al, 2011;Huang, Chen, et al, 2011;Huang et al, 2014;Kim et al, 2012;Kunnumakkara et al, 2012;Mohebati et al, 2012;Rafailov et al, 2007;Sandur et al, 2007;Yan et al, 2012;Yang et al, 2007Yang et al, , 2008 reveal diverse mechanisms of action, possibly explaining its robust effects using in vivo models of tumorigenesis at oral doses that mimic human intakes (Huang, Chen, et al, 2011;Kunnumakkara et al, 2012). Because herbal extracts are composed of multiple compounds, it is difficult to directly extrapolate a standard concentration.…”
Section: Fig 3 -Regulation Of Downstream Targets Of Ampk By Aicar Inmentioning
confidence: 85%
See 3 more Smart Citations
“…Our data pertaining to Zyflamend and several studies from other laboratories (Bemis et al, 2005;Burke et al, 2015;Capodice et al, 2009;Ekmekcioglu et al, 2011;Huang, Chen, et al, 2011;Huang et al, 2014;Kim et al, 2012;Kunnumakkara et al, 2012;Mohebati et al, 2012;Rafailov et al, 2007;Sandur et al, 2007;Yan et al, 2012;Yang et al, 2007Yang et al, , 2008 reveal diverse mechanisms of action, possibly explaining its robust effects using in vivo models of tumorigenesis at oral doses that mimic human intakes (Huang, Chen, et al, 2011;Kunnumakkara et al, 2012). Because herbal extracts are composed of multiple compounds, it is difficult to directly extrapolate a standard concentration.…”
Section: Fig 3 -Regulation Of Downstream Targets Of Ampk By Aicar Inmentioning
confidence: 85%
“…Its original formulation almost 2 decades ago was based on those herbs that had antioxidant and antiinflammatory properties. Its subsequent use in experimental investigations in an assortment of cancer models has drawn attention by a variety of laboratories interested in the role of natural products in health and disease (Bemis et al, 2005;Burke et al, 2015;Capodice et al, 2009;Ekmekcioglu et al, 2011;Huang, Chen, et al, 2011;Huang et al, 2014;Kim et al, 2012;Kunnumakkara et al, 2012;Mohebati et al, 2012;Rafailov et al, 2007;Sandur et al, 2007;Yan et al, 2012;Yang et al, 2007Yang et al, , 2008. There are always concerns regarding reproducibility and quality control of commercial products.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies have shown significant differences in patterns of eicosanoid metabolism between different types of malignant tissues; for example, it has been shown that colon cancer is regulated in part by the relative expression of 13-S-hydroxyoctadecadienoic acid (13-S-HODE; ref. 14), that glioblastomas invariably overexpress 5-LOX, 6 and that prostate cancer is connected to an age-associated decline in the expression of 15-hydroxyeicosatetraenoic acid (15-HETE), a tumor suppressor (15), as well as up-regulation of 12-LOX which, in turn, inhibits Rb tumor suppressor activity (16).…”
mentioning
confidence: 99%